ANALYSIS OF INVESTMENT OPPORTUNITY SET AND FORM SIZE TOWARDS DIVIDEND POLICY ON MINING COMPANY LISTED IN INDONESIA STOCK EXCHANGE (IDX) PERIOD 2015 - 2017 - Ciseta Yoda, Tilawatil (MENARA EKONOMI, 2019)
This is descriptive quantitative research aimed to see how the influence of investment opportunity set and form size on dividend policy on mining companies listed on the Indonesia Stock Exchange 2015-2017 period. The population in the study were all mining companies listed on the Indonesian Stock Exchange in the period 2015-2017, while the sampling technique used was purposive sampling method in order to obtain a sample of 14 companies. Data analysis techniques used in this research is multiple linear regression. The results indicate that the investment opportunity set, and the form size partially and  imultaneously influence the dividend policy. Investment Opportunity Set a partial positive effect on dividend policy whereby 8.814 t count> t table 2.024 and 0.000 significant value <0.05 while the size of the company partially negative effect on dividend policy whereby -5.708 and t count> t table -2.024 and significant value 0,000 <0,05 . From these results, it is expected the manager to make decisions in the future be paying particular attention to the investment opportunity and the form size so that it can determine the appropriate dividend policy.Keywords: Investment Opportunity Set, form size, Dividend Policy.